Enrichment of Platinum Group Elements in Lower Cambrian Polymetallic Black Shale, SE Yangtze Block, China - Fu, Yong; Yang, Zhen; Li, Chao; Xia, Peng (Frontiers in Earth Science, 2021)
Platinum group elements (PGEs) occur mainly in basic–ultrabasic igneous rocks and are concentrated by the differentiation and crystallization of magma. Thin polymetallic layers including Ni, Mo, V, PGEs, and rare-earth elements are widely developed in lower Cambrian black shales in southern China. The PGE contents in such layers may not be economically significant but are still unusually enriched. PGE enrichment mechanisms have not been widely studied, but here the PGE compositions of polymetallic layers in the Shuidong (Nayong) and Niuchang (Weng’an) sections of the SE Yangtze block in China were determined, and results compared with published data for the region. Results indicate that PGEs are enriched in the polymetallic layers, whereas the surrounding country rocks are barren. The ΣPGE contents in the Shuidong Ni–Mo deposits are generally lower than in the Niuchang V deposits. PGE distribution patterns in the polymetallic layers are similar to those in basic–ultrabasic rocks, indicating that such rocks played a role in the PGE enrichment. Oceanic hypoxia during the Sinian–Cambrian transition resulted in the production of large amounts of organic matter and H2S in the ocean. When high-salinity brine reached the ocean bottom, rapid changes in Eh–pH conditions caused enrichment of metals at the sediment–seawater interface, and this enrichment was later enhanced during diagenesis.